The Importance of Halal Labeling in Consumer Food and Beverage Purchasing Decisions Based on Demographic Factors: A Case Study of Minimarket Consumers in Palembang City - Wahyudi, Bayu; Yasmin, Yasmin; Putri, Anindita Rahmalia; Aziz, Zakaria Nur; Andrean, Ari (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2025)
This study aims to explore the significance of halal labeling in food and beverage purchasing decisions at minimarkets in Palembang, Indonesia, with a particular focus on the factors influencing Muslim consumers' choices. The research employed a descriptive survey design, utilizing an online questionnaire to collect data from 155 respondents over a one-month period. Demographic information, including age, gender, educational level, and religion, was gathered alongside questions about the prioritization of halal labels in purchasing decisions. Descriptive statistical analysis was used to process the data. The findings reveal that the halal label is the most influential factor in consumers' purchasing decisions, followed by price and taste. Gender did not significantly affect the prioritization of the halal label, while age and educational level showed variations in preference, with younger and less-educated respondents placing more emphasis on halal certification. The study highlights the dominant role of religious beliefs in shaping purchasing behavior, particularly among Muslim consumers. The research has implications for marketers and retailers, emphasizing the importance of halal certification in product offerings, especially in regions with a predominantly Muslim population. However, the study's limitations include its reliance on a non-probability sampling method and a homogenous respondent pool, which may not fully represent the broader population's preferences.